PENGEMBANGAN VIDEO PEMBELAJARAN MATERI INTEGRAL PADA PEMBELAJARAN FLIPPED CLASSROOM - Marfi Ario; Azmi Asra (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
Integral material is an important material to be mastered by mathematics education students. The purpose of this study is to produce integral material learning videos that are valid, practical, and effective for use in flipped classroom learning. This research is a development research consisting of 5 phases, namely: initial investigation; design; realization/ construction; testing, evaluation and revision; implementation. The instruments in this study were questionnaires filled with material and instructional media experts to measure validity, questionnaires filled by students using video to measure practicality, and test questions to measure the effectiveness of learning videos. The results of this study showed that the learning videos developed are valid with very good criteria, practical and effective with good criteria. The findings of this study also showed that the use of video learning on the flipped classroom can optimize the time of classroom learning to discuss material more broadly and deeply.